Melatonin’s Effect in Febrile Seizures and Epilepsy - MAHYAR, Abolfazl; AYAZI, Parviz; DALIRANI, Reza; GHOLAMI, Nargess; DANESHI-KOHAN, Mohammad Mahdi; MOHAMMADI, Navid; AHMADI, Mohammad Hossein; SAHMANI, Ahmad Ali (Iranian Journal of Child Neurology, 2014)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE FA <![endif]--> How to Cite This Article: Mahyar A, Ayazi P, Dalirani R, Gholami N, Daneshi-Kohan MM, Mohammadi N, Ahmadi MM, Sahmani AA. Melatonin’s Effect in Febrile Seizures and Epilepsy Iran J Child Neurol. 2014 Summer;8(3): 24-29. Abstract Objective Recognition of risk factors for febrile seizures (FS) and epilepsy is essential. Studies regarding the role of melatonin in these convulsive disorders are limited. This study determines the relationship between serum melatonin levels and FS and epilepsy in children. Materials & Methods A population of 111 children with simple FS, complex FS, and epilepsy (37 children per group, respectively) were included as case groups. In addition, 37 febrile children without seizures comprised the control group. Serum melatonin levels were measured and compared between all groups. Results The serum melatonin levels in the simple, complex FSs, and epilepsy groups were 2, 2.4, and 2 pg/ml, respectively. The serum melatonin level in the control group was 2.1pg/ml. Moreover, there were no significant differences observed while comparing the case groups. Conclusion The present study reveals that there is no association between serum melatonin level and simple or complex FS and epilepsy. It appears that melatonin plays no significant role in these convulsive disorders. References Banerjee TK, Hazra A, Biswas A, Ray Jet al. Neurological disorders in children and adolescents. Indian J Pediatr2009; 76:139-46. Salehi Omran MR, Khalilian E, Mehdipour E, Ghabeli JA. Febrile seizures in North Iranian children: Epidemiology and clinical feature, Journal of Pediatric Neurology2008, 6: 39-43. Shinnar S, O’Dell C. Febrile Seizures, Pediatr Ann 2004, 33: 394-402. Millar JS. The child with febrile seizure, Pediatrics for parents 2006.24:12-14. Fetvei A. Assessment of febrile seizures in children, Eur J Pediatr2008, 167:17-27. Mikati MA. Seizures in Childhood In: Kliegman RM, Stanton BF, Schor NF, St. Geme III JW, Behrman RE. Nelson textbook of pediatrics. 19th ed. Phila: Saunders, 2011:2013-2039. Camfield PR, Canfield CS. Epilepsy. In: Swaiman KF, Ashwal S, Ferriero DM, editors. Pediatric neurology: principles and practice. 4th ed. Philadelphia: Mosby, 2006:981-8. Chang BS, Lowenstein DH. Epilepsy, N Eng J Med 2003, 13:1257-1266. Aydin A, Ergor A, Ergor G, Dirik E. The prevalence of epilepsy amongst school children in Izmir, Turkey, Seizure 2002; 11: 392–396. 10.Jan MM, Girvin JP. Febrile seizures. Update and controversies. Neurosciences (Riyadh) 2004; 9:235-42. French JA. Febrile seizures: possible outcomes. Neurology2012; 28; 79:e80-2. Guo JF,Yao JF. Serum melatonin levels in children with epilepsy or FS, Zhongguo Dang Dai Er Ke Za Zhi2009, 11:288-90 (Medline). Reiter RJ. Melatonin: clinical relevance, Best Pract. Res Clin Endocrinol Metab 2003, 17: 273-285. Seithikurippu R, Perumal P, Trakh I, Srinivasan V, Spence DW, Maestroni GJM, Zisapel N, Cardinali DP. Physiological effects of melatonin Role of melatonin receptors and signal transduction pathways, Prog Neurobiol 85, 2008: 335-353. Ardura J, Andres J, Garmendia JR, Ardura F. Melatonin in epilepsy and FS.J Child Neurol 2010; 25:888-91. Ganesh R, Janakiraman L, Meenakshi B. Serum zinc levels are low in children with simple FS compared with those in children with epileptic seizures and controls.Ann Trop Paediatr 2011; 31:345-9. Bazil CW, Short D, Crispin D, Zheng W. Patients with intractable epilepsy have low melatonin, which increases following seizures. Neurology 2000; 55:1746-8. Yalyn O, Arman F, Erdogan F, Kula M. A comparison of the circadian rhythmsand the levels of melatonin in patients with diurnal and nocturnal complexpartial seizures. Epilepsy Behav 2006;8:542-6. Schapel GJ, Beran RG, Kennaway DL, McLoughney J, Matthews CD. Melatonin response in active epilepsy. Epilepsia 1995; 36:75-8. Ekmekcioglu C. Melatonin receptors in humans: biological role and clinical relevance,Biomedicine and Pharmacotherapy 2006,60: 97-108. Tan DX, Manchester LC, Hardeland R, Lopez-Burillo S, et al. Melatonin: a hormone, a tissue factor, an autacoid, a paracoid, and an antioxidant vitamin. J Pineal Res 2003; 34:75-8. Allegra M, Reiter RJ, Tan DX, Gentile C, et al. The chemistry of melatonin’s interaction with reactive species. J Pineal Res 2003; 34:1-10. Rodriguez C, Mayo JC, Sainz RM, Antolin I, et al. Regulation of antioxidant enzymes: a significant role for melatonin. J Pineal Res 2004; 36:1-9. Tan DX, Reiter RJ, Manchester LC, Yan M.T et al. Chemical and physical properties and potential mechanisms: melatonin as a broad spectrum antioxidant and free radical scavenger, Curr Top Med Chem2002, 2:181-197. Molina-Carballo A, Munoz-Hoyos A, Sanchez-Forte M, Uberos-Fernandez J,Moreno-Madrid F, Cuna-Castroviejo D. Melatonin increases following convulsive seizures may be related to its anticonvulsant properties at physiological concentrations, Neuropediatrics 2007; 38:122–5. Molina-Carballo A, Acuña-Castroviejo D, Rodríguez- Cabezas T, Muñoz-Hoyos A. Effects of febrile and epileptic convulsions on daily variations in plasma melatonin concentration in children. J Pineal Res 1994; 16: 1-9 Rao ML, Stefan H, Bauer J. Epileptic but not psychogenic seizures are accompanied by simultaneous elevation of serum pituitary hormones and cortisol levels. Neuroendocrinology 1989; 49:33-9. Fauteck J, Schmidt H, Lerchl A, Kurlemann G, Wittkowski W. Melatonin in epilepsy: first results of replacement therapy and first clinical results. Biol Signals Recept 1999; 8:105–10. Peled N, Shorer Z, Peled E, Pillar G. Melatonin effect on seizures in children with severe neurologic deficit disorders. Epilepsia 2001; 42:1208–10. Coppola G, Iervolino G, Mastrosimone M, La TG, et al. Melatonin in wake-sleep disorders in children, adolescents and young adults with mental retardation with or without epilepsy: a double-blind, cross-over, placebo-controlled trial. Brain Dev 2004; 26:373-6. <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->